THE ADDITION INTERVENTION IN PALM KNEADING MASSAGE, SHORT WAVE DIATHERMI, TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION AND MC. KENZIE EXERCISE REDUCE BACK PAIN LUMBAL DISC BULGING - Bhayu Wirawan, I Made (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 3 (2013): Majalah Ilmiah Fisioterapi Indonesia, 2013)
This research aimed to identifi addition intervention in palm kneading, short wave diathermi, transcutaneous electrical nerve stimulation and Mc. Kenzie exercise reduce back pain lumbal disc bulging. Method : This research is using pre test and post test control group design. Patients were randomised into two groups : the Control Group (CG) that use SWD, TENS and Mc.Kenzie exercise is 11 patients. The Experimental Group (EG) that SWD, TENS, Mc.Kenzie exercise and palm kneading massage is 11 patients too. Result : The result of CG test which using compare means with paired sample t-test, p<0,05 (p=0,000) that mean the intervention in CG is having significant to reduce pain. In the result of EG test which using compare means with paired sample t- test, p<0,05 (p=0,000) that mean the intervention in EG is having significant to reduce pain. The result test researcher using compare mean test with Independent sample t-test, p<0,05 (p=0,021), that means there are significant different between EG result and CG result. In one tail hypothesis got result p<0,05, so it shows that intervention in EG more effective significantly than CG in to reduce pain  disc bulging lumbal. Conclusion : Addition intervention in palm kneading, short wave diathermi, transcutaneous electrical nerve stimulation and Mc. Kenzie exercise reduce back pain lumbal disc bulging.
Keywords: reduce pain lumbal, palm kneading